Correction of cytokine misbalance between pro-inflammatory TNF-α and anti- inflammatory IL-4 in patients with chronic generalized periodontitis - Khudiakova, Maryna (Khudiakova M. Correction of cytokine misbalance between pro-inflammatory TNF-α and anti-inflammatory IL-4 in patients with chronic generalized periodontitis / M. Khudiakova // the 6th International USERN Congress and Prize Awarding Festival : abstract, mTalk and poster books, Istanbul, 6th–13th of November 2021. – Istanbul, 2021. – P. 298., 2021)
The cytokine level of the patients with initial and I degrees of severity in the basic group after six-month treatment was TNF-α - 27,51 ± 2,57 pg/ml, which was 107 % higher than in the C groups and anti-inflammatory ІL-4 - 292,2 ± 20,77 pg/ml, which was 19 % lower than in the C groups. The cytokine level of the patients in the comparison group after six-month treatment was TNF-α - 32,72 ± 3,56 pg/ml, which was 109 % higher than in the C groups and anti-inflammatory ІL-4 - 261,7 ± 16,25 pg/ml, that was 17 % lower than in the C groups.
Keywords: pro-inflammatory TNF-α; pro-inflammatory TNF-α; anti-inflammatory IL-4; anti-inflammatory IL-4; lecithin liposomes; lecithin liposomes; chronic generalized periodontitis; chronic generalized periodontitis; quercetin; quercetin